Strategies of Increasing Local Taxes in the North Central Timor District - Yohanes B.D. Banu; David B.W. Pandie; Petrus Kase (Program Pascasarjana Universitas Negeri Makassar, 2020)
This research was conducted to determine the strategy for increasing local taxes implemented by the Regional Revenue Agency of Timor Tengah Utara Regency. The results of this research show that the regional taxes of North Central Timor Regency have not been running optimally because of the 9 (nine) types of taxes not all of them have contributed to the Regional Original Income. A strategy for increasing local taxes through intensification and extensification is needed. Intensification includes 1) aspects of institutional arrangement, 2) aspects of management which include processing regional tax data, determining regional tax data as well as collecting and collecting local taxes. 3) personnel aspects. while the extensification aspect is related to data collection and verification as well as socialization of local taxes. Furthermore, the ratio of the contribution of local taxes to the regional revenue of North Central Timor Regency is still insufficient, the local taxes that contribute the most to local revenue are street lighting taxes while the least contributed taxes are groundwater taxes. In the implementation of regional taxes, there are several supporting factors in the form of the availability of adequate facilities and infrastructure, adequate budget and cooperation with State-Owned Enterprises (BUMN) and Regional-Owned Enterprises (BUMD), while the inhibiting factor is the low awareness of taxpayers, unscrupulous officials. dishonest and not yet integrated local tax information system with regional income.